FOLHETOS COMO FERRAMENTA DE EDUCOMUNICAÇÃO EM PARQUES NATURAIS: ESTUDO DE CASO SOBRE OS PARQUES DE CANELA/RS - Stahnke, Leonardo Francisco; Costa, Vania Medianeira Flores (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
In this article was analyzed the leaflets in the Natural Paks of Canela/RS, and its itsrelationship with the “Educommunication” and Sustainable Tourism. Thus, initially were identifiedthe parks with relevant natural characteristics and, with support from the Tourist InformationCenter, we obtained access to their promotional materials. Each leaflets was then evaluated bycomparison, based on a matrix of 53 criteria, without the three focus of analysis: GeneralInformation, Design and Environmental Education. Of the 17 national parks listed, only seven hadinformation leaflets, one of the state and six private. From this study it was found that the parksdo not know how to produce publicity materials of the “educommunication”, getting all leafletswell below the proposed criteria. In order to address this deficit, we propose a Guide toSustainable Tourism for the national parks of this city.